Pseudomonas aeruginosa Syntrophy in Chronically Colonized Airways of Cystic Fibrosis Patients - Qin, Xuan (American Society for Microbiology, 2012)
Pseudomonas aeruginosa isolates from cystic fibrosis (CF) patients undergo remarkable phenotypic divergence over time, including loss of pigmentation, hemolysis, motility, and quorum sensing and emergence of antibiotic hypersusceptibility and/or auxotrophism. With prolonged antibiotic treatment and steady decline in lung function in chronically infected patients, the divergent characteristics associated with CF isolates have traditionally been regarded as “adapted/unusual virulence,” despite the degenerative nature of these adaptations. We examined the phenotypic and genotypic diversity in clonally related isogenic strains of P. aeruginosa from individual CF patients. Our observations support a novel model of intra-airway pseudomonal syntrophy and accompanying loss of virulence. A 2007 calendar year collection of CF P. aeruginosa isolates (n = 525) from 103 CF patients yielded in vitro MICs of sulfamethoxazole-trimethoprim (SMX-TMP, which typically has no activity against P. aeruginosa) ranging from 0.02 to >32 μg/ml (median, 1.5). Coisolation of clonally related SMX-TMP-susceptible and -resistant P. aeruginosa strains from the same host was common (57%), as were isogenic coisolates with mutations in efflux gene determinants (mexR, mexAB-oprM, and mexZ) and genes governing DNA mismatch repair (mutL and mutS). In this cohort, complete in vitro growth complementation between auxotrophic and prototrophic P. aeruginosa isogenic strains was evident and concurrent with the coding sequence mosaicism in resistance determinants. These observations suggest that syntrophic clonal strains evolve in situ in an organized colonial structure. We propose that P. aeruginosa adopts a multicellular lifestyle in CF patients due to host selection of an energetically favorable, less-virulent microbe restricted within and symbiotic with the airway over the host's lifetime.